All‐Inorganic Metal Halide Perovskite Nanostructures: From Photophysics to Light‐Emitting Applications. Issue 1 (27th November 2017) - Wang, Yue; Sun, Handong
Abstract: All‐inorganic metal halide perovskite nanostructures (IHPNs) have sparked intense research interest by virtue of their superior optical properties and their cost‐effective synthesis. Since the first report in 2015, striking development of IHPNs has been witnessed in terms of fabrication strategies, optical characterization, and optoelectronic applications. Here, a brief survey of the mainstream fabrication routes is given. The emphasis is placed on the understanding of the photophysics of IHPNs, including the electronic structures, steady‐state and transient absorption and emission, nonlinear optical properties, and representative exotic photophysical phenomena. Afterward, the light‐emitting applications of IHPNs in lasers and light‐emitting diodes are summarized. Finally, the challenges and a perspective of the future development of IHPNs are presented. Abstract : All‐inorganic metal halide perovskite nanostructures (IHPNs) have sparked intense research interest by virtue of their superior optical properties and their cost‐effective synthesis. Since the first report in 2015, striking development of IHPNs has been witnessed in terms of fabrication strategy, optical characterization, and optoelectronic applications.